The voice of students from a Black, Asian or minority ethnic background. (9th December 2021) - Simons, Joan; Belton, Silice Patrice
The Open University is a large, distance-learning university, serving all four nations of the United Kingdom (UK) and provides education for most of its students through open entry, meaning that no prior qualifications are necessary. At the OU, we have a low percentage of students who come from a black, Asian or minority ethnic (BAME) background, ranging from 4% to 13% depending on their programme of study. However, due to the high student population at the Open University, that low percentage amounts to thousands of students. We were keen to hear from our BAME students, as we are aware of a challenging awarding gap between these students and white students. We ran three focus groups with a total of ten students from a BAME background, and asked about issues such as being valued, inclusion, a sense of belonging and feeling represented. This was the first time that BAME students had been asked about their views in this way. We found that although there were positive insights, students were uncomfortable engaging in forums, lacked a sense of belonging and did not feel represented in the curriculum. By encouraging these students to give voice to their concerns, we heard, for the first time, some of the issues they are dealing with that need to be addressed.